Mycotoxin exposure assessments in a multi-center European validation study by 24-hour dietary recall and biological fluid sampling. (April 2020) - De Ruyck, Karl; Huybrechts, Inge; Yang, Shupeng; Arcella, Davide; Claeys, Liesel; Abbeddou, Souheila; De Keyzer, Willem; De Vries, Jeanne; Ocke, Marga; Ruprich, Jiri; De Boevre, Marthe; De Saeger, Sarah
Highlights: All study subjects were exposed to between 4 and 34 mycotoxins. Agreement among different multi-mycotoxin internal and external exposure measurements was explored in a human population. Significant correlations were observed between mycotoxin concentrations in serum and urine. Quantitative agreements between serum and urine were observed for trichothecenes and zearalenone. Abstract: The European Food Consumption Validation (EFCOVAL) project includes 600 men and women from Belgium, the Czech Republic, France, the Netherlands, and Norway, who had given serum and 24-hour urine samples, and completed 24-hour dietary recall (24-HDR) interviews. Consumption, according to 24-HDR, was matched against the European Food Safety Authority (EFSA) databases of mycotoxin contaminations, via the FoodEx1 standard classifications, producing an indirect external estimate of dietary mycotoxin exposure. Direct, internal measurements of dietary mycotoxin exposure were made in serum and urine by ultra-performance liquid chromatography coupled to tandem mass spectrometry. For the first time, mycotoxin exposures were thoroughly compared between two 24-HDRs, and two 24-hour urine samples collected during the same days covered by the 24-HDRs. These measurements were compared to a single-time point serum measurement to investigate evidence of chronic mycotoxin exposure. According to 24-HDR data, all 600 individuals were exposed to between 4 and 34 mycotoxins, whereof 10 found to exceed the tolerable daily intake. Correlations were observed between two time points, and significant correlations were observed between concentrations in serum and urine. However, only acetyldeoxynivalenol, ochratoxin A, and sterigmatocystin were found to have significant positive correlations between 24-HDR exposures and serum, while aflatoxin G1 and G2, HT-2 toxin, and deoxynivalenol were associated between concurrent 24-HDR and 24-hour urine. Substantial agreements on quantitative levels between serum and urine were observed for the groups Type B Trichothecenes and Zearalenone . Further research is required to bridge the interpretation of external and internal exposure estimates of the individual on a time scale of hours. Additionally, metabolomic profiling of dietary mycotoxin exposures could help with a comprehensive assessment of single time-point exposures, but also with the identification of chronic exposure biomarkers. Such detailed characterization informs population exposure assessments, and aids in the interpretation of epidemiological health outcomes related to multi-mycotoxin exposure.